Urban transformation stories for the 21st century: Insights from strategic conversations. (May 2018) - Moglia, Magnus; Cork, Steven J.; Boschetti, Fabio; Cook, Stephen; Bohensky, Erin; Muster, Tim; Page, Declan
Highlights: We explore the future of cities from a resilience perspective. Six dominant urban adaptive cycles are identified. These represent often dysfunctional urban transformations. To provide a positive and constructive vision, we define a reflexive city narrative. Abstract: It is commonly argued that cities face unprecedented pressures and therefore must transform. To guide transformations, it is important to develop guiding visions. This paper reports on a futures thinking exercise in the context of cities. It employs a methodology based on a series of community workshops with a diverse mix of experts using a "strategic conversation". The conversation was framed around the question: 'How might your city build and maintain resilience in a range of plausible futures?' Results of the process help to identify risks and opportunities, as well as urban transformation archetypes. Furthermore, these narratives are interpreted as city reorganization patterns similar to those theorized in resilience thinking through the notion of adaptive cycles. Finally, the possibility of developing a more functional transformation narrative for cities is outlined, which would enable the development of a collective vision for a desired urban future and how to avoid the adverse consequences of drivers of change in cities.